COMPARING THE EFFECTIVENESS OF TWO APPROACHES IN LEARNING ENGLISH IN INDONESIA - Nita Rosmala Dewi; Sota Yamamoto; Seo Jiwon; Thabo Mokoena (Yayasan Adra Karima Hubbi, 2025)
The teaching of English as a foreign language in Indonesia continues to face challenges, particularly in identifying the most effective instructional approach. Previous studies have shown varying results when comparing communicative and grammar-based methods in language acquisition. This study aims to compare the effectiveness of two dominant approaches: the Communicative Language Teaching (CLT) method and the Grammar-Translation Method (GTM) in improving English proficiency among secondary school students in Indonesia. Employing a quasi-experimental design, this research involved 120 students divided into two equal groups, each receiving instruction based on one of the approaches over a period of 12 weeks. Pre-tests and post-tests were administered to measure students’ progress in reading, writing, listening, and speaking skills. The results indicated that the CLT group significantly outperformed the GTM group, particularly in speaking and listening components, while the GTM group showed marginally better results in grammar and reading comprehension. The findings suggest that while both methods have merits, CLT offers a more balanced improvement in communicative competence. This study contributes to the ongoing discourse on English pedagogy in EFL contexts and provides evidence-based recommendations for curriculum development in Indonesian schools.